Sunflower festival: its origin, significance and impact to the ligaoenos - Consulta, Marulyn R. (San Miguel, Iriga City: University of Saint Anthony, 2015)
Sunflower festival: its origin, significance and impact to the ligaoenos.
Includes bibliographical references.
English
Keywords: Origin